2016
DOI: 10.7150/ijbs.15781
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Thymoquinone against Cyclophosphamide-Induced Hemorrhagic Cystitis through Inhibiting DNA Damage and Upregulation of Nrf2 Expression

Abstract: Cyclophosphamide (CYP) induced hemorrhagic cystitis is a dose-limiting side effect involving increased oxidative stress, inflammatory cytokines and suppressed activity of nuclear factor related erythroid 2-related factor (Nrf2). Thymoquinone (TQ), an active constituent of Nigella sativa seeds, is reported to increase the expression of Nrf2, exert antioxidant action, and anti-inflammatory effects in the experimental animals. The present study was designed to explore the effects of TQ on CYP-induced hemorrhagic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 37 publications
6
37
1
Order By: Relevance
“…In models of CYP-induced urotoxicity, DADS treatment exhibited a notable upregulation of bladder Nrf2/HO-1/NQO-1 protein expression (Kim et al, 2014) and a similar result was observed with a medicinal plant derived from Nigella sativa seeds (F: Ranunculaceae) called thymoquinone which possessed an antioxidant activity and showed a marked rise in the bladder protein expression of Nrf2 (Gore et al, 2016).…”
Section: Effects Of Cypsupporting
confidence: 61%
See 2 more Smart Citations
“…In models of CYP-induced urotoxicity, DADS treatment exhibited a notable upregulation of bladder Nrf2/HO-1/NQO-1 protein expression (Kim et al, 2014) and a similar result was observed with a medicinal plant derived from Nigella sativa seeds (F: Ranunculaceae) called thymoquinone which possessed an antioxidant activity and showed a marked rise in the bladder protein expression of Nrf2 (Gore et al, 2016).…”
Section: Effects Of Cypsupporting
confidence: 61%
“…Kim et al (2014) reported that CYP induced a marked upregulation of bladder Nrf2/HO-1/NQO-1 protein expression reporting that urotoxicity induced Nrf2 with concomitant phase II enzymes as a cytoprotective mechanism (Kim et al, 2014). A contradictory study showed decreased bladder protein expression of Nrf2 accompanied with CYP injection and explained this action through CYP metabolites, which diminish the Nrf2 activity and subsequently inhibit phase II antioxidant enzymes resulting in increased oxidative tissue damage (Gore et al, 2016). These controversial results could be attributed to different study designs including the difference in the CYP dose and the experimental animals used.…”
Section: Effects Of Cypmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (2012) proved that the CP produced significant DNA damage and cell apoptosis in mouse bone marrow cells and peripheral blood leukocytes, DNA damage, and cell apoptosis were investigated by single cell gel electrophoresis, flow cytometry assay with annexin V-FITC/propidine iodide (PI), and acridine orange (AO)/ethidium bromide (EB) staining assay. Gore et al (2016) investigated the effect of CP on bladder genomic DNA by agarose gel electrophoresis in mice, and they found that genomic DNA samples isolated from bladders of mice treated with cyclophosphamide showed significantly greater DNA fragmentation. Cell apoptosis is involved in the CP-induced acute hepatotoxicity, characterized by activation of immunohistochemical marker caspase-3, a key cell death protease (Li et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…TQ treatment administered intraperitoneally in the doses of 5, 10, and 20 mg/kg before and after the cyclophosphamide injections prevented histological perturbations as evidenced by decreased cellular infiltration, edema, epithelial denudation and hemorrhage in the bladder tissue, reduced oxidative stress, lipid peroxidation and inhibited DNA fragmentation. TQ also induced Nrf2 expression in the bladder tissues of mice concomitant to the restored anti-oxidant s in the bladder tissues (Gore et al, 2016 ).…”
Section: Pharmacological Potentials Of Thymoquinonementioning
confidence: 99%